The Geopolitics of Energy: Out with the Old and in with the New? - Bassam Fattouh; Ahmed Mehdi; Michal Meidan (Oxford Energy Forum: A Quarterly Journal for Debating Energy Issues and Policies, 2021)
Gathering momentum for the energy transition has sparked debate on what the energy map will look like in 30 years. For more than half a century now, access to oil and natural gas has been at the heart of the geopolitics of energy; but with renewable technologies set to dominate energy supply systems, relations between states will change, while economies and societies will undergo structural transformations. This issue of the Oxford Energy Forum discusses the drivers and main features of the 'old' and 'new' geopolitics of energy. It assesses the power shifts that are unfolding, the winners and losers—both countries and technologies—that are likely to emerge from this process, and the potential implications for global governance regimes. Our authors ask whether the prospects of peak oil demand will dim the geopolitical forces shaping producer–consumer relations and upend geopolitical arrangements which have been defining elements of regional power systems. They ask: who will lead the race for new technologies and supply chains? And how will US–China competition and coordination impact global efforts to meet the Paris climate goals? A thread running through this Forum is a warning against intellectual complacency. One key theme is that assumptions about the future geopolitical outlook of countries, regions, and trade relationships will hardly be guided by history, given the size and scope of the transformation. Demand-side policy and capital allocation shifts will create both challenges and opportunities for fossil fuel incumbents—a stark reminder that while some regions are moving more slowly, no region is standing still as the energy transition gathers pace. Similarly, identifying winners and losers is not as clear-cut as it seems, especially in light of concerns that the US is losing out in the race with the EU and China. The third theme serves as a stark reminder that the pathways to net zero will be neither linear nor uniform, especially in light of the falling costs of technologies. But the race for technological leadership and for control of the supply chains of new materials will become a key factor in the geopolitics of new energies.
Keywords: 330